2007
DOI: 10.1016/j.rmed.2007.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of inflammatory biomarkers in asthma: Exhaled nitric oxide and induced sputum eosinophil count

Abstract: The diagnostic accuracy of FE(NO) measurement was superior to that of the standard diagnostic spirometry in patients with symptoms suggestive of asthma. The use of FE(NO) measurement and induced sputum Eos% together to diagnose asthma in clinical practice is more accurate than spirometry or FE(NO) assessment alone and easier to perform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…A further three studies 80,81,92 were identified from the update search. Four of these studies 70,77,87,95 included data for FeNO testing in conjunction with another test.…”
Section: Diagnostic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A further three studies 80,81,92 were identified from the update search. Four of these studies 70,77,87,95 included data for FeNO testing in conjunction with another test.…”
Section: Diagnostic Reviewmentioning
confidence: 99%
“…l Nine studies 54,[69][70][71][72][82][83][84]86,87,90 recruited patients with symptoms of asthma who were broadly equivalent to patients entering the UK pathway at position A (see Figure 8). Of these, six 69,71,72,[82][83][84]86,87 were considered to be of most relevance to the decision problem, although the studies had not necessarily been conducted in the UK.…”
Section: Studies Meeting the Inclusion Criteriamentioning
confidence: 99%
“…It has been found to be elevated in patients with atopic asthma (i.e., asthma associated with either positive skin test or specific IgE to aeroallergens) and was shown to correlate modestly with eosinophilia in sputum and endobronchial biopsy in steroid-naïve patients. [7][8][9][10][11] It has also been found to be elevated in both children and adults with atopy without a diagnosis of asthma, (eg atopic rhinitis). 12,13 FeNO levels in atopic patients appear to correlate with number of positive skin prick tests and tests of bronchial hyperresponsiveness.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Fractionally Exhaled Nitric Oxide (FeNO), on the other hand, is a less invasive assay that measures the exhaled nitric oxide, thereby indirectly assessing the level of inflammation in the airways. Nevertheless, the level of diagnosis based upon FeNO decreases in patients with smoking habits or other OAD (46,47).…”
Section: Serum Biomarkers For Asthmamentioning
confidence: 99%